Postmodern narrative in Kurt Vonneguts Slaughterhouse-Five - Abu Jweid, Abdalhadi Nimer Abdalqader; Ali Termizi, Arbaayah; Majeed, Abdulhameed A. (American Research Institute for Policy Development, 2015)
This article explores Kurt Vonnegut’s Slaughterhouse-Five (1969) as a postmodern critique of modern literary modes. As a novel recapitulating within itself a postmodern relative perspective of reality, it elucidates one aspect of postmodernism, that of literary experimentation. Vonnegut experiments with the narrator,setting and characters of the novel to provide a fictional critique of the literary exhaustion prevailing in modern literary modes. Experimentation is thus remedial replenishment for such exhaustion through authorial metafictional intrusion into the text. Accordingly, the article uses Patricia Waugh, Gérard Genette and Mikhail Bakhtin’s narrative theory to examine the experimental technique in the novel. What makes the majority of metafictional style unique is not only its presence in the novel, but also its conflated depiction of the American individual’s suffering after the Second World War.For this later style, the self-justifying manner in the novel extrapolates textual dialogic relations to accentuate the author’s critical voice. Such voice originates in the main narrative point of view in the text and is known as focalization.